First inventory of sea anemones (Cnidaria: Actiniaria) from La Paz Bay, southern Gulf of California (Mexico) - Barragán, Yamaly; Sánchez, Carlos; Rodríguez, Estefanía (Zootaxa, 2019)
Sea anemones from the Mexican Pacific are poorly known. We report and redescribe eight species of sea anemones from La Paz Bay in the southern Gulf of California, Mexico. As a result of this inventory, we validate records for 30 species from the Mexican Pacific, 23 of them from the Gulf of California and 15 of those present in La Paz Bay. We provide taxonomic diagnoses, images of internal and external anatomy, size ranges and types of cnidae, and geographic and bathymetric distribution, and discuss the taxonomic diagnostic characters for each species. This study is the first illustrated inventory of sea anemones from La Paz Bay.